PELAYANAN PENCATATAN PERNIKAHAN DI SUMATERA BARAT PASCA PEMBERLAKUAN PP NOMOR 48 TAHUN 2014 - Muhammad Agus Noorbani (Balai Penelitian dan Pengembangan Agama Jakarta, 2019)
Abstract This paper is the result of research on marriage registration services in West Sumatra after the enactment of Government Regulation Number 48 of 2014. Marriage registration services have a high significance, thus encouraging the government to pay serious attention to these services and make various efforts to continue to improve the quality of these services. Among these efforts is the issuance of Government Regulation (PP) Number 48 of 2014 concerning Amendment to Government Regulation Number 47 of 2004 concerning Tariffs on Types of Non-Tax State Revenues Applicable to the Ministry of Religion, which was later revised with Government Regulation Number 19 of 2015 concerning Types and Tariff for Types of Non-Tax State Revenues that Apply to the Ministry of Religion. Since this regulation was promulgated, the number of marriages in the Office of Religious Affairs (KUA) has increased significantly. Using a comparative or cross-case study design, this study seeks to find out the service of registering marriages in eight KUA in West Sumatra. This study found that there was an increase in the number of marriages in KUA during working hours. The implementation of the fee amount based on this new regulation has also been carried out by each KUA. The enactment of this regulation has not yet had an impact on the improvement of marriage registration services at KUA. This is because the management of marriage costs has been allocated more often for honorariums for professional services and transportation of marriage registration officers outside the KUA. There has been no allocation for the improvement of facilities and infrastructure of the KUA building to improve marriage registrar services.